The Shift in Penal Paradigm: The Implementation of Restorative Justice in Resolving Minor Theft Cases in Indonesia - Ramandha Mudest; Mimin Mintarsih (Faculty of Law, University of Dr. Soetomo, 2026)
The Indonesian criminal justice system has traditionally relied on retributive paradigms that often marginalize the needs of victims, particularly in minor theft cases. In such instances, formal legal proceedings frequently fail to facilitate direct restitution and can inadvertently exacerbate social friction. Addressing this gap, this study analyzes the implementation of restorative justice in petty theft cases, evaluating its efficacy through a victimological lens. Employing a normative legal framework with a descriptive-analytical methodology, the research utilizes statutory, conceptual, and case approaches grounded in comprehensive library research. The findings reveal that restorative justice introduces a crucial paradigm shift—humanizing the legal process by prioritizing loss recovery and the restoration of social harmony over punitive measures. Legally underpinned by Attorney General Regulation No. 15 of 2020 and Police Regulation No. 8 of 2021, this framework successfully fosters peaceful dispute resolution, direct offender accountability, and tangible restitution. Ultimately, the study concludes that restorative justice constitutes an effective, victim-centric alternative that resonates with modern victimological principles, provided it consistently balances restorative goals with stringent legal certainty and victim protection.